Indian academy of pediatrics (neonatology chapter) recommendations for evidence-based neonatal skincare and protocols for hospitalized neonates - Bajaj, Naveen; Kumar, R. Kishore; Inamadar, Arun; Bhandari, Alok; Kumar, Rajesh; Uttam, Kheya Ghosh; Mittal, Jaikrishan; Suryawanshi, Pradeep; Wazir, Sanjay; Hemrajani, Satyen; Thakor, Priti (Frontiers in Pediatrics, 2025)
IntroductionInfants in a neonatal intensive care unit (NICU) face a significant risk of skin barrier damage due to various factors related to their condition and the medical interventions they receive. The Neonatology Chapter of the Indian Academy of Pediatrics aimed to develop a comprehensive guidance document on evidence-based clinical practices for neonatal skin care in hospitalized infants, focusing on scientific principles and empirical evidence.MethodThe modified Delphi method, involving a panel of 10 experts including neonatologists and pediatricians, was utilized to reach a consensus on clinical statements.ResultsOut of 132 clinical statements formulated, 127 achieved consensus, while 5 did not. The experts advised implementing screening tools and risk assessment frameworks for skin injuries as part of the NICU's quality of care assessment. They emphasized the need for gentle cleansing of newborns to prevent skin or eye irritation and reduce the risk of skin infections. When determining the mode and method of skin cleansing in neonates, factors such as weight, gestational age (GA), and the severity of illness should be taken into account. Emollients may effectively prevent transepidermal water loss (TEWL) and be well-tolerated by NICU infants. Considering topical emollient therapy may significantly reduce mortality and hospital-acquired infections and improve weight gain. Multisensory stimulation in preterm infants has the potential to enhance feeding, psychomotor development, and visual function. Providing parents with a booklet that includes skincare regimens for cleansing the baby and protecting the skin barrier is essential for home care of their baby.ConclusionThis consensus aims to fill this void by offering clinical recommendations for the care of neonatal skin in hospitalized infants.